Pengaruh Piutang Usaha , Modal Dan Hutang Jangka Panjang Terhadap Laba Bersih Pada Perusahaan Otomotif Yang Terdaftar Di Bei Tahun 2019-2022 - Nur Azizah; Elyanti Rosmanidar; Ferri Saputra Tanjung (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
This study aims to determine the effect of account receivable, equity, and non-current liabilities on net income in food and beverage manufacturing companies listed on the Indonesia Stock Exchange in 2019 -2022. This study uses independent variables, namely account receivable, equity, and non-current liabilities. The dependent variable is net profit. The data used in this study is secondary data, namely in the form of financial reports of automotive and component companies listed on the IDX for 2019-2021. 2019 is used to compare 2020 to 2022. This research is descriptive with a quantitative approach. Statistical methods using multiple linear regression analysis, t test, f test, and analysis of the coefficient of determination.The results of this study indicate that account receivable, equity, and non-current liabilities partially have effect on net income. Then account receivable, equity, and non-current liabilities simultaneously also have effect on net income. By using the F test it was found that the independent variables did not have a simultaneous effect on the dependent variableFrom the determination calculation, the Adjusted R Square value is 0.553 or 55,3% . This means that it indicates that the variables of ccount receivable, equity, and non-current liabilities on net income have an effect of 55.3% and the remaining 44.7% can be influenced by other factors outside of this study.